2012
DOI: 10.1371/journal.pone.0030175
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Inosine Triphosphatase Activity Is Decreased in HIV-Seropositive Individuals

Abstract: BackgroundInosine triphosphatase (ITPase) is encoded by the polymorphic gene ITPA and maintains low intracellular levels of the inosine nucleotides ITP and dITP. The most frequently reported polymorphisms are ITPA c.94C>A (rs 1127354) and ITPA c. 124+21 A>C (rs7270101). Some nucleoside-analogues used in the treatment of HIV-seropositive (HIV+) patients are potential substrates for ITPase. Therefore, the frequency of ITPA SNPs and ITPase activity were studied in a population of HIV+-patients.MethodsThe study po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, in accordance with our previous work [ 29 ] we found that an ITPA variant such as wt/c.124+21A>C lead to a variety of ITPase activities from as low as 1.53 to as high as 7.70 mmol IMP/mmol Hb/hour. Moreover, in spite of wt/wt genotype, HIV-infected patients were found to have a decreased ITPase activity compared to control patients [ 16 ] and therefore more often will have an ITPase activity <4 mmol IMP/mmol Hb/hour. In HIV, the association between ITPA genotype and ITPase activity is less strict as has previously been assumed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in accordance with our previous work [ 29 ] we found that an ITPA variant such as wt/c.124+21A>C lead to a variety of ITPase activities from as low as 1.53 to as high as 7.70 mmol IMP/mmol Hb/hour. Moreover, in spite of wt/wt genotype, HIV-infected patients were found to have a decreased ITPase activity compared to control patients [ 16 ] and therefore more often will have an ITPase activity <4 mmol IMP/mmol Hb/hour. In HIV, the association between ITPA genotype and ITPase activity is less strict as has previously been assumed.…”
Section: Discussionmentioning
confidence: 99%
“…ITPase activity was expressed as mmoles of IMP formed from ITP in one hour per mmol hemoglobin (mmol IMP/mmol Hb/hour). The cut-off value discriminating between normal or decreased ITPase activity was set at 4 mmol IMP/mmol Hb/hour, which is the lowest value within the 95% CI for ITPA wt/wt carriers [ 16 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzyme inosine triphosphate pyrophosphatase (ITPase) is an example of a degradative response. ITPAse hydrolyzes inosine‐5′‐triphosphate (ITP) into a monophosphate, prevents appearance of hypoxanthine base in DNA . The importance of ITPases has been highlighted in every kingdom of life.…”
Section: Introductionmentioning
confidence: 99%